2019
DOI: 10.3389/fpsyg.2019.00541
|View full text |Cite
|
Sign up to set email alerts
|

The Summer Undergraduate Research Experience as a Work-Integrated Learning Opportunity and Potential Pathway to Publication in Psychology

Abstract: Unlike disciplines which focus on skill development from year one of a bachelor’s degree, training in psychology in Australia follows the scientist-practitioner model. According to this model, an undergraduate psychology degree should focus on the scientific principles underpinning the discipline and provide a foundation for the development of professional skills in graduate school. However, most Australian psychology undergraduates do not continue into graduate school, and concerns have been raised about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…My experiences support observations made by other scholars: Despite various forms of support, only a few collaborative projects with undergraduate students lead to publications (e.g., Banegas et al, 2020; Garside et al, 2015; Golding et al, 2019; Harrington et al, 2015). While I attempt to guide all students that I supervise through the steps and elements of phase one in the process, very few are successful.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…My experiences support observations made by other scholars: Despite various forms of support, only a few collaborative projects with undergraduate students lead to publications (e.g., Banegas et al, 2020; Garside et al, 2015; Golding et al, 2019; Harrington et al, 2015). While I attempt to guide all students that I supervise through the steps and elements of phase one in the process, very few are successful.…”
Section: Discussionsupporting
confidence: 77%
“…Undergraduate students do not have experience to turn their papers into a journal article (Golding et al, 2019; McKelvie & Standing, 2019), so I take the lead in developing strategies for revisions and editing. However, students have to choose how much time and effort they plan to spend in this phase.…”
Section: Phase Two: Post‐defencementioning
confidence: 99%
See 1 more Smart Citation
“…We propose that institutions can simultaneously situate skill development in STEM and provide meaningful, work-like experience through undergraduate research experiences (UREs). Though UREs are not generally recognized as work-integrated learning (WIL), UREs have been suggested as a form of WIL (Golding et al, 2019). UREs are high-impact practices (Kuh et al, 2017) with well-established impact on student self-perceptions and career decisions (Lopatto, 2004;Russell et al, 2007;Seymour, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, students perceive that they have learned collaboration and communication skills, the ability to apply clinical reasoning skills, and presentation skills in problem-based learning (Schwartz et al, 1997;Khan and Fareed, 2001). Research among psychology students have shown that generic skills have been learned in working life (Golding et al, 2019). However, generic skills have been examined less among psychology students.…”
Section: Introduction Learning Generic Skillsmentioning
confidence: 99%